Books, not bombs : teaching peace since the dawn of the republic - Howlett, Charles F.; Harris, Ian M. (Peace education., 2010)
Books Not Bombs: Teaching Peace Since the Dawn of the Republic is an important work relevant to peace scholars, practitioners, and students. This incisive book offers an exciting and comprehensive historical analysis of the origins and development of peace education from the creation of the New Republic at the end of the Eighteenth Century to the beginning of the Twenty-First century. It examines efforts to educate the American populace, young and old, both inside the classroom and outside in terms of peace societies and endowed organizations. While many in the field of peace education focus their energies on conflict resolution and teaching peace pedagogically, Books Not Bombs approaches the topic from an entirely new perspective. It undertakes a thorough examination of the evolution of peace ideology within the context of opposing war and promoting social justice inside and outside schoolhouse gates. It seeks to offer explanations on how attempts to prevent violence have been communicated through the lens of history.